2009
DOI: 10.2169/internalmedicine.48.2220
|View full text |Cite
|
Sign up to set email alerts
|

Peginterferon (PEG-IFN) Plus Ribavirin Combination Therapy, but neither Interferon nor PGE-IFN Alone, Induced Type 1 Diabetes in a Patient with Chronic Hepatitis C

Abstract: Interferon (IFN) therapies, including IFN, peginterferon (PEG-IFN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] We reviewed the data for each of these cases, focusing on the length of time from the start of IFN+RBV therapy to the onset of type 1 diabetes mellitus, continuation/discontinuation of IFN therapy after the onset of type 1 diabetes, weaning/nonweaning from insulin therapy after discontinuation of IFN+RBV, presence/ absence of pancreas-associated auto antibodies before and after IFN+RBV therapy, and the HLA haplotype of the patients ( Table 1). While in most cases IFN+RBV therapy had been discontinued immediately after the diagnosis of type 1 diabetes, 3,[8][9][10][11][12][13][14][15][16]18,[20][21][22][23][24] the treatment had been continued in two cases, including the present case. 25 Insulin therapy could be discontinued later in only two of the 19 cases in which IFN+RBV therapy had been stopped immediately after the diagnosis of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] We reviewed the data for each of these cases, focusing on the length of time from the start of IFN+RBV therapy to the onset of type 1 diabetes mellitus, continuation/discontinuation of IFN therapy after the onset of type 1 diabetes, weaning/nonweaning from insulin therapy after discontinuation of IFN+RBV, presence/ absence of pancreas-associated auto antibodies before and after IFN+RBV therapy, and the HLA haplotype of the patients ( Table 1). While in most cases IFN+RBV therapy had been discontinued immediately after the diagnosis of type 1 diabetes, 3,[8][9][10][11][12][13][14][15][16]18,[20][21][22][23][24] the treatment had been continued in two cases, including the present case. 25 Insulin therapy could be discontinued later in only two of the 19 cases in which IFN+RBV therapy had been stopped immediately after the diagnosis of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ogihara et al . reported that adding ribavirin on IFN therapy could be a trigger for type 1 diabetes, 11 the potency of IFN per se to impair β‐cell function should be kept in mind especially for the treatment of aged CHC patients using a small dose of PEG‐IFN for a prolonged period.…”
Section: Discussionmentioning
confidence: 99%
“…RBV also has immunomodulatory effects, but RBV is rarely used as monotherapy. However, there is a case report describing a patient who developed T1D after RBV was added to Peg-IFN ( 126 ).…”
Section: Pancreatic Islets Autoimmunity – Type 1 Diabetes and Hepatitmentioning
confidence: 99%